HIV, highly active antiretroviral therapy and the heart: a cellular to epidemiological review. Issue 6 (26th November 2015) - Lambert, CT; Sandesara, PB; Hirsh, B; Shaw, LJ; Lewis, W; Quyyumi, AA; Schinazi, RF; Post, WS; Sperling, L
Abstract : The advent of potent highly active antiretroviral therapy (HAART) for persons infected with HIV‐1 has led to a "new" chronic disease with complications including cardiovascular disease (CVD). CVD is a significant cause of morbidity and mortality in persons with HIV infection. In addition to traditional risk factors such as smoking, hypertension, insulin resistance and dyslipidaemia, infection with HIV is an independent risk factor for CVD. This review summarizes: (1) the vascular and nonvascular cardiac manifestations of HIV infection; (2) cardiometabolic effects of HAART; (3) atherosclerotic cardiovascular disease (ASCVD) risk assessment, prevention and treatment in persons with HIV‐1 infection.